The Influence of Classroom Management on the Learning Outcomes of Students in the Department of Office Management and Business Services at SMK Negeri 4 Makassar - Riska Alfiana; Muh. Nasrullah; Sitti Hardiyanti Arhas (Journal of Educational Development and Learning (JEDAL), 2025)
This study analyzes the correlation between classroom management and students’ learning outcomes in the Department of Office Management and Business Services at SMK Negeri 4 Makassar. A quantitative associative approach was employed with 63 respondents selected from a population of 75 students. Data were collected through questionnaires, observations, interviews, and documentation and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results show that classroom management and learning outcomes are categorized as satisfactory and high, respectively. The correlation coefficient (r = 0.278) indicates a positive but low correlation, with a determination value (R² = 0.077) meaning that classroom management explains only 7.7% of the variation in learning outcomes. Although the effect size is relatively small, the relationship is statistically significant (p < 0.05), suggesting that well-organized classroom environments contribute to better academic achievement. This study highlights that other factors beyond classroom management also influence learning outcomes. The novelty of this research lies in its focus on classroom management within vocational education, which differs from regular schools due to its applied learning orientation and discipline-based environment. The findings contribute to understanding how classroom organization supports effective learning in vocational settings.